Influência da usabilidade para melhora da produtividade no uso de prontuário eletrônico do paciente no setor de cardiologia do HUSM - Zen, Eliana (2008)
The Electronic Patient Record was created with the intention to facilitate and to improve the performance of doctors and professionals that provide health care. Its goal is to facilitate the clinical and administrative information access and sharing, to help on the decision taken process, as well as to support the scientific studies. In order, the professionals of the HUSM Cardiology sector decided to create a computerized system to their patients registering. This process started with a Data Bank construction developed by the own medical team of the Intensive Cardiology Unit. Meanwhile, Software Usability aspects weren t observed and the result was a not user friendly data insertion interface, tookking to a down productivity than the expected. According the Usability Engineering principles, an Electronic Patient Record system should be of easy learning and memorization, allowing an efficient use and avoiding the users errors. When these characteristics are considered in software development, better productivity levels and users satisfaction are gotten. This work explores the Usability Engineering theory to get a productivity improvement on registering clinical information on HUSM Cardiology sector. For such, it evaluates the usability of the existing data bank interfaces, in order to verify its strong and weak points, it models and implements a new version of the system, this time based on the usability principles and on the users profile that will use it, and realizes a new usability evaluation of the new software version. As result, a reduction is observed on the users error average (37,5%) and on the necessary time to realize some pre-established tasks (33%), besides the increase on the percentage of well succeed tasks (13%). We also have observed an increasing on users satisfaction because the percentage of users that had declared to be find problems or difficulties when using the system reduce from 100% to 28%. These results show the use of usability engineering techniques on development of the Electronic Patient Record gets direct influence on health professionals productivity.